Freedom is, freedom ain't : jazz and the making of the sixties - Saul, Scott (African American music reference., 2003)
"In the long decade between the mid-1950s and the late 1960s, jazz was changing more than its sound. The age of Max Roach's Freedom Now Suite, John Coltrane's A Love Supreme, and Charles Mingus's The Black Saint and the Sinner Lady was a time when jazz became both newly militant and newly seductive, its example powerfully shaping the social dramas of the civil rights movement, the Black Power movement, and the counterculture. Freedom Is, Freedom Ain't is the first book to tell the broader story of this period in jazz - and American - history."--Jacket.